Protein nutritive utilization in goats with and without exclusion of rumen and reticulum (Revista Española de Fisiología, 1979)
The digestive utilization of protein in fistulated goats has been studied through a system of three cannulae. The protein digestibility coefficient is greater with casein in the rumen than with it in the abomasum, explainable by a higher ammonium production. On the other hand, with casein in the abomasum the duodenal digest contains more protein, and aminoacid composition improves in quality and quantity. The differences found in the above mentioned results are mainly due to a rumen bacterial action upon aminoacids and the subsequent absorption of the ammonium formed.